2015
DOI: 10.24908/pceea.v0i0.5813
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Student Retention and Attrition Literature Review

Abstract: The University of Saskatchewan, similar tomany engineering colleges, would like to improve studentretention. With that in mind, a literature review wasundertaken to summarize current peer reviewed literaturerelated to engineering student retention and attrition inan attempt to better understand the potential structuralcauses, processes, and student characteristics that maycontribute to student success or attrition. Through asystematic search of several major databases using thekeywords “engineering and attriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…There is a strong link between students feeling that their instructors care about their success as engineers, and retention/student success [4] [10]. The participants echoed the literature strongly; when instructors make them feel unwelcome and seem to not care about teaching their courses, it becomes a barrier to their success.…”
Section: Instructor Levelmentioning
confidence: 91%
See 3 more Smart Citations
“…There is a strong link between students feeling that their instructors care about their success as engineers, and retention/student success [4] [10]. The participants echoed the literature strongly; when instructors make them feel unwelcome and seem to not care about teaching their courses, it becomes a barrier to their success.…”
Section: Instructor Levelmentioning
confidence: 91%
“…what we should "stop" doing, we asked them to identify if there was anything specific that came to mind when they thought of potential barriers to their success in engineering. After coding 180 meaningful answers and grouping them into similar themes, we found that the students' answers could be funneled further into the categories that emerged from the literature review [4]: student level, instructor level, and college level These categories were adapted from what Robert Marzano calls the three levels of factors that influence elementary and high school effectiveness [5].…”
Section: Stopmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite myriad efforts, students from groups underrepresented in engineering are still less likely to persist, relative to their peers. [1][2][3][4][5][6][7][8][9][10] To address this, many programs have incorporated design projects early in the curriculum, leading to higher overall retention of diverse students in engineering. [11][12][13][14][15][16][17][18][19][20][21][22][23] For instance, students from underrepresented groups were likelier to persist if they completed a first year design course, and this was attributed to the hands-on and contextual nature of the experience 12 .…”
Section: Introduction and Purposementioning
confidence: 99%